PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN BEBAN KERJA TERHADAP KETERIKATAN KARYAWAN SERTA IMPLIKASINYA TERHADAP KINERJA KARYAWAN PADA PT BANK SYARIAH MANDIRI KOTA PEKANBARU - Boby Maihendra; Jumiati Sasmita; Raden Lestari Garnasih (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2019)
This study aimed to examine and analyze the influence of leadership , organization culture and workload on performance with employee enggagement as intervening variable. The study was conducted in PT. Bank Syariah Mandiri Pekanbaru city. The data used consist of primary and secondary data. Data were collected by using questionnaires that given to 104 employees of PT. Bank Syariah Mandiri Pekanbaru city that used Census Sample. Descriptive analysis method is used to describe the characteristics of respondents and the research hyphotheses by using relevant statistical tests. Variables used are leadership , organization culture and workload as independent variable, performance as dependent variable and employee enggagement to intervening or mediation variable. Analyzer used is path analysis by using program of SPSS 21 for windows. The results of this study conclude that leadership has a direct influence significantly on performance, the culture organization directly influence not significantly to performance and employee enggagement have a significant effect on performance. Indirectly, employee enggagement has positive mediation role on the influence of leadership on performance and employee enggagement has a positive mediation role on the influence of organization culture on performance and employee enggagement has a positive mediation role on the influence of workload on performance . The improvement effectiveness of leadership , organization culture and workload and are recommended in order to optimize employee performance and motivation.